Understanding and Overcoming Barriers to Small Business Growth: Nigerian Evidence - Umaru Mustapha Zubairu; Friday Ogbole; Afisat Ayorinde; Mohammad Dokochi (IJEBD International Journal Of Entrepreneurship And Business Development eISSN 2597-4785 pISSN 2597-4750)
Purpose: This study sought to understand the barriers hindering the growth of small businesses in Nigeria, and to investigate the various strategies small business owners and managers develop to overcome these barriers. Design/methodology/approach: A qualitative research design using in-depth, semi-structured, face-face interviews was utilized to obtain the barriers to growth as well as strategies developed to overcome them by 15 sachet water company managers in Minna, the capital city of Niger State in North Central Nigeria. Findings: The major internal barriers to growth identified included unmotivated employees, lack of modern machinery, lack of storage capacity and poor marketing and distribution strategies, while the major external barriers included weather conditions, poor electricity, bad roads and competition. Strategies to overcome these barriers included creating a family atmosphere, hiring more workers, using alternative power and forming a union to control prices. Research limitations/implications: This study was limited to 15 sachet water companies in Minna, Niger State, so it is difficult to generalize the findings to other states and to other industries. Practical implications: The results of this study will be beneficial to several stakeholders: sachet water companies in Minna and beyond, other SMEs as well as policy makers. For sachet water companies in Minna and beyond, by understanding the various strategies which the interviewed managers use to overcome their internal and external challenges, a diffusion of learning will occur, whereby other sachet water company managers can inculcate some of these effective strategies into their own operations. As for other SMEs, some of the identified barriers will also be the same ones they face. The strategies the interviewed managers use to overcome these challenges can also provide guidance for these SMEs. Finally, by clearly identifying the barriers hindering the growth of these sachet water companies, this study provides policy makers with clear guidance on what policies need to be instituted to help these SMEs overcome their challenges and contribute their quota to the growth of the Nigerian economy. Originality/value: By utilizing semi-structured interviews in surveying the 15 sachet water managers in Minna, Niger State, this study overcomes the weakness of the vast majority of prior studies which utilized questionnaires. The major disadvantage of adopting questionnaire to measure attitudes and perception is that, respondents will be denied the opportunity to air out their views about the subject matter.